EFFECT OF BRAZIL NUT (BERTHOLLETIA EXCELSA) SUPPLEMENTATION ON HUMAN HEALTH: A SYSTEMATIC REVIEW - Rodrigues, Denise Cristina; Correa, Kely de Paula; Medeiros, Hiasmyne Silva de; Franceschini, Sylvia do Carmo Castro; Stringheta, Paulo Cesar; Coimbra, Jane Sélia dos Reis (International Journal of Research -GRANTHAALAYAH, 2021)
Previous studies suggest that Brazil nut can improve the nutritional status of selenium, reduce oxidative stress, modify lipid profile, and alter inflammatory markers. A systematic review was performed to evaluate and synthesize the results of studies on the effect of Brazil nut supplementation on human health. The review was conducted according to the recommendations of the Preferred Reporting Items for reviews and was based on searches of the databases BIREME, BMC Proceedings, The British Library, The Cochrane Library, and PubMed up to December 2019. The searches also included at the databases Google Scholar and Web of Sciences. The descriptors were identified using the Health Science Descriptors system and the search strategy included the following combination of keywords: Bertholletia, protein, lipid, nutritive value, and selenium; in English and Portuguese. A total of 510 potential studies were screened, of which 25 studies were considered for this review. All studies showed that supplementation with Brazil nut in the amounts evaluated improved the selenium status in the body and had positive effects without reports of adverse effects. This systematic review indicates that Brazil nut has a beneficial effect on human health, but further studies with double-blind controlled clinical trials and larger sample sizes are needed for the validation of these effects.